Time-varying Integration of Stock Markets from Global and Regional Perspective in Asia-Pacific - Hayun Kusumah; Marwan Asri; Kusdhianto Setiawan; Bowo Setiyono (University of Merdeka Malang, 2021)
This study investigates the time-varying integration of stock markets from a global and regional perspective, the consequences of two major global financial crises, i.e., the Asian Financial Crisis and the subprime mortgage, and the Crisis triggered by COVID-19. We contribute to the growing amount of literature on market integration, especially on the role of regional to global market integration. Although regional integration encourages an acceleration of global integration, the effect of a regional factor is not uniform among regions. It is important to understand regional to global market integration and the consequences during the crises. This study employs time-series data from economic territories based on the Morgan Stanley Capital International (MSCI) Asia-Pacific classification. It introduces an alternative measurement of time-varying integration by considering the correlation of regional and global markets using a simple international model, equivalent to the capital asset pricing model (CAPM). The result shows that the market integrations are time-varying both globally and regionally. The domestic markets are affected by the global market and its regional market, as the role of a regional market emerges during the financial crisis period. We find the different responses of stock markets during the Covid-19 period as a dominant factor to exacerbate the market return globally. In the long run, the upward trend for the regional market integration in both developed and emerging markets is inherent to the global market integration.DOI: 10.26905/jkdp.v25i3.5822